Virulence, Antimicrobial Susceptibility, Molecular and Epidemiological Characteristics of a New Serotype of Vibrio parahaemolyticus From Diarrhea Patients - Zhu, Qiaoyun; Chen, Xiao; Liu, Yanchao; Wang, Ruonan; Chen, Jiayao; Chen, Yu (Frontiers in Microbiology, 2020)
Vibrio parahaemolyticus is the main pathogen of food-borne diarrheal in coastal areas. Through the study of pathogen characteristics of 1870 V. parahaemolyticus, the isolation rate of O4:KUT had increased significantly since 2013. In this study, we analyzed virulence, antimicrobial susceptibility, molecular and epidemiological characteristics of a new serotype named O4:KUT2. O4:KUT2 strains had tlh+ tdh+ trh- toxRS/new- characteristics and were prevalent during 2013 to 2015. 91.5% O4:KUT2 serotype strains were resistant to ampicillin. The growth curves of O4:KUT2 strains were different with O4:K9, O4:K8 and O3:K6 serotype strains. O4:KUT2 strains belonged to ST332 where four strains had a large fragment inserted at recA. Compared the whole genomes of O4:KUT2 strains with O4:K9 strain which also belonged to ST322 isolated from acute diarrhea patients in Zhejiang province in 2012, no different alleles at 2249 loci was found. This finding implied that O4:KUT2 strains might be derived from O4:K9 strains. Clinical presentation of patients positive for V. parahaemolyticus O4:KUT2 were no significant difference with patients positive for O3:K6, although their genetic characteristics were different. The appearance and the increase of proportion of the new serotype O4:KUT2 strains was aware that we should not relax the monitoring of the pathogen spectrum of acute diarrheal patients.